Analysis of Pedagogical-Digital Competence in Teacher Educators: Practices and Perceptions - Lorena Berríos-Barra; Margarita Calderón-López (Revista Latinoamericana de Tecnología Educativa)
The digital competence of future teachers has been a concern of public policy in Chile, reflected in the development of Information and Communication Technology (ICT) standards that emphasize the importance of incorporating digital technologies pedagogically in initial teacher education (ITE). A lack of digital pedagogical skills has been reported among teachers in training (Silva et al., 2019). The development of digital teaching competence (DTC) also involves those who train teachers. This study focuses on exploring the beliefs of university professors to analyze their impact on the use of technologies in ITE. A Sequential Exploratory Design (DEXPLOS), combining qualitative and quantitative methods, was conducted with teacher trainers. Content analysis was performed in the qualitative phase (n=13), and factorial analysis in the quantitative phase (n=67) using a questionnaire. The results reveal advances in the ethical and digital citizenship aspects of the DTC of the participating teacher trainers but do not suggest a reflective approach during practice, which affects the development of agency among future teachers. In summary, the didactic integration of digital technologies is not evident. The guidelines for didactic-digital competence highlight the importance of promoting and integrating these skills into teaching practices as an essential requirement to improve the conditions of children and adolescents facing the uncertainty of the 21st century.